Myth of the Westminster model. - GHANY, Hamid (1994)
Argues that the British Government introduced, not the Westminster model, but a completely unique system of Government for the ex-colonies at their imdependence. Identifies and describes that system which was subsequently retained, thereby proving the myth of the existence of the Westminster model in the English-speaking Caribbean.